Architectonics and parametric modeling : computational modeling for beginning design /: computational modeling for beginning design. (2023) - Jacobus, Frank; Carpenter, Angie; Di Nunzio, Antonello; Bedeschi, Francesco; Loerts, Rachel Smith
No abstract available